Hubungan Kepercayaan Diri Terhadap Ketepatan Servis Atas Bola Voli - Ramadani, Desta; Juita, Ardiah; Rusmanto, Rusmanto (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
In a volleyball match, serve is the primary attacking move as an important tactic, and confident players can better manage pressure because they can stay focused and serve accurately. This study aims to ensure the relationship between self-confidence and service accuracy in volleyball extracurricular participants at SMP Negeri 5 Pekanbaru. Correlational research was the method used in the study, with a sample of 27 students playing volleyball as an extracurricular activity. Google Forms surveys are used to collect data on trust factors, and AAHPER Service Tests are used to assess the accuracy of the best service. The process of evaluating hypotheses involves various correlation analyses. With a value of 0.549 > 0.381, the findings showed a strong relationship between confidence and service accuracy in volleyball extracurricular players at SMP Negeri 5 Pekanbaru. It was found that an athlete's main drive to excel is their high level of confidence. Early development of self-confidence is essential because confident athletes can perform better and reach their full potential in sports.